Hyperfine interaction measurements on ceramics: PZT revisited - Guarany, Cristiano A.; Araujo, Eudes B.; Silva, Paulo R. J.; Saitovitch, Henrique (Elsevier B.V., 2007)
The solid solution of PbZr1-xTixO3, known as lead-zirconate titanate (PZT), was probably one of the most studied ferroelectric materials, especially due to its excellent dielectric, ferroelectric and piezoelectric properties. The highest piezoelectric coefficients of the PZT are found near the morphotropic phase boundary (MPB) (0.46 <= x <= 0.49), between the tetragonal and rhombohedral regions of the composition-temperature phase diagram. Recently, a new monoclinic phase near the MPB was observed, which can be considered as a bridge between PZT's tetragonal and rhombohedral phases. This work is concerned with the study of the structural properties of the ferroelectric PZT (Zr/Ti = 52/48, 53/47) by hypertine interaction (HI) measurements obtained from experiments performed by using the nuclear spectroscopy time differential perturbed angular correlation (TDPAC) in a wide temperature range. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: PZT ceramics; nuclear spectroscopy; hyperfine interactions